2014
DOI: 10.1002/hrm.21630
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Discriminatory Climate Perceptions on the Composition of Intraorganizational Developmental Networks, Psychosocial Support, and Job and Career Attitudes of Employees with an Invisible Stigma

Abstract: Recent diversity research recognizes that employees' social identity and perceptions of diversity openness and support shape their career experience and decisions. To build further on this line of work, this study aims to advance an understanding of the impact of discriminatory climate perceptions on the social relationships at work and work-related attitudes of employees with an invisible stigma. To achieve this purpose and test hypotheses, professional lesbians and gay men were selected as a representative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 94 publications
(201 reference statements)
2
52
0
7
Order By: Relevance
“…This is a conservative estimate, given that LGBT identities can be invisible and, as a result, some LGBT employees decide to conceal their identities (King, Mohr, Peddie, Jones, & Kendra, ). Indeed, deciding whether to disclose at work is often a challenging process that is accompanied by fear and anxiety due to the stigma associated with LGBT identities (Ragins, Singh, & Cornwell, ; Trau, ). Although public perceptions of LGBT people have become increasingly more positive in the United States, a large portion of Americans (45%) still believe that being gay is a sin (Drake, ), and attitudes toward gender nonconformity are even more unfavorable (Norton & Herek, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is a conservative estimate, given that LGBT identities can be invisible and, as a result, some LGBT employees decide to conceal their identities (King, Mohr, Peddie, Jones, & Kendra, ). Indeed, deciding whether to disclose at work is often a challenging process that is accompanied by fear and anxiety due to the stigma associated with LGBT identities (Ragins, Singh, & Cornwell, ; Trau, ). Although public perceptions of LGBT people have become increasingly more positive in the United States, a large portion of Americans (45%) still believe that being gay is a sin (Drake, ), and attitudes toward gender nonconformity are even more unfavorable (Norton & Herek, ).…”
Section: Introductionmentioning
confidence: 99%
“…A study about bullying showed that being bystanders of workplace bullying might affect observers’ health negatively (Vartia, 2001; Hoel et al, 2004; Lutgen-Sandvik et al, 2007). Moreover, research carried out with lesbian and gay (LG) professionals (Trau, 2015) demonstrated that a discriminatory climate might be perceived by workers, which in turn might have consequences at personal and organizational levels (Ragins, 2004). Perceiving a discriminatory environment might be considered a stressor, even if people do not experience discrimination directly.…”
Section: Introductionmentioning
confidence: 99%
“…Nesse mesmo sentido, o E4 revela um entendimento de que as mulheres são mais receptivas aos homossexuais, ao contrário dos homens broncos da Engenharia, que são os que desenvolvem atividades tidas como essencialmente masculinas. Sua fala (E4) reforça a importância do ambiente (HUFFMAN et al, 2008;LUCAS;KAPLAN, 1994;TRAU, 2015) para a decisão de abertura da identidade sexual no trabalho.…”
Section: Apresentação E Análise Dos Resultadosunclassified
“…Embora grande parte das pesquisas (HUFFMAN; WATROUS-RODRIGUEZ; KING, 2008;LUCAS;KAPLAN, 1994;TRAU, 2015) sugira que um clima organizacional que favorece a afirmação da identidade sexual promove resultados positivos para o empregado, o coming out nem sempre é visto como a melhor opção do empregado. Isso porque o preconceito e atitudes homofóbicas ainda se fazem muito presentes nas organizações (BICALHO; DINIZ, 2009;CAPRONI et al, 2014;GARCIA;SOUZA, 2010;IRIGARAY et al, 2010).…”
Section: Razões E Efeitos Do Coming Outunclassified
See 1 more Smart Citation